Hirschsprung’s disease: epidemiology, diagnosis, and treatment in a retrospective hospital-based study - Andi Sinapati Palissei; Ahmadwirawan Ahmadwirawan; Muhammad Faruk (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Hirschsprung’s disease (HD), or congenital megacolon, is a disease characterizedby the absence of ganglion cells in the myenteric (Auerbach’s) and submucosal(Meissner’s) plexuses of the intestine, causing maximum obstruction inneonates. The purpose of this study was to investigate patient characteristics,clinical presentation, investigations, surgical treatment, and outcome. Thisstudy is a retrospective study of HD cases. Data obtained from medical recordsat the institution. Of the 109 with a positive rectal biopsy diagnosis, 91 werepatients with this disease. There were more cases in boys than girls with aratio of 1.37: 1. The patients were grouped into 4 age groups: neonates 29 cases(26.61%); infants/toddlers/young children 55 cases (50.46%); children over 5years16 cases (14.69%); and teenagers 9 cases (8.24%). The neonates generallypresented with abdominal distension, green vomiting, and a history of delayedmeconium release, while the toddler, child, and adolescent groups experiencedconstipation and abdominal distension. Furthermore, from 37 patients (33.94%)that got barium enema examination, the most common transition zone wasobserved in the rectosigmoid (17 patients, or 45.9%). In addition, The Duhamelprocedure was the most frequent pull-through procedure found in our cohortwhich was performed in 40 patients (36.70%). In conclusion, HD is mostly foundin male infants/toddlers/young children with abdominal distention and chronicconstipation as common symptoms. The barium enema shows the rectosigmoidas the most common transition zone, while the Duhamel pull-through procedureis the primary definitive operative action performed.